Semiotic Analysis on Flannery O’connor’s A Good Man is Hard to Find - Ni Luh Ade Ulan Antari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The title of this study is Semiotic Analysis on Flannery O’Connor’s A Good Man Is Hard to Find. This study focuses on the analysis of icons, indexes, and symbols in the short story. The data was taken from A Good Man Is Hard to Find short story. This study analyzes the sign based on three of the six sign species in Signs: An Introduction to Semiotics (Sebeok, Second Edition 2001), these three species are Charles Peirce's classification of signs, namely icon, index, and symbol. This study used the documentation method for collecting data. In analyzing the data, this study applied the qualitative method to present the data because the data was collected in the form of words and was analyzed based on the theory applied in this study using words and sentences. In presenting the data, quotes from the short stories are used as the data. The result shows the icons, indexes, and symbols found in the short stories. There are a total of thirteen data in this study, including four data for icons, seven data for indexes, and two data for symbols.